الحبة السوداء في ضوء السنة النبوية وعلم الطب - Mesbahul Hoque; Abdoul Karim Toure; Zulhilmi Mohamed Nor; Shumsudin Yabi (Universiti Sains Islam Malaysia, 2024)
Journal of Islamic Social Sciences and Humanities Volume 30 Issue 1 Page (25-38)